2018
DOI: 10.1097/jhm-d-16-00034
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Comprehensive Wellness Assessment on Medication Adherence in a Medicare Advantage Plan Diabetic Population

Abstract: The issue of medication nonadherence has generated significant interest because of its complexity from both cost and outcomes perspectives. Of the 3.2 billion prescriptions written annually in the United States, estimates indicate that half are not taken as prescribed, especially among patients with asymptomatic chronic conditions. The objective of this study was to assess whether a comprehensive wellness assessment (CWA) program helps improve medication adherence for oral diabetic medications, statins, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Similarly, Faridi et al [ 25 ] showed that providing a first outpatient visit in the first week after discharge after a hospitalization for ST-elevation myocardial infarction or a non-ST-elevation myocardial infarction had a positive effect on patient adherence in patients when compared to first outpatient visits that took place more than 6 weeks after discharge. On the other hand, results by Guerard et al [ 26 ] and Kooy et al [ 27 ], using a comprehensive wellness assessment program or patient counselling combined with an electronic reminder device respectively, did not show any impact on statin adherence. Of note, although general results were inconclusive, Kooy et al [ 27 ] did report that using only the electronic reminder device had a positive effect on patient adherence in women in a secondary prevention setting (adjusted OR = 8.26 [2.20–31.0], p = 0.002).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Similarly, Faridi et al [ 25 ] showed that providing a first outpatient visit in the first week after discharge after a hospitalization for ST-elevation myocardial infarction or a non-ST-elevation myocardial infarction had a positive effect on patient adherence in patients when compared to first outpatient visits that took place more than 6 weeks after discharge. On the other hand, results by Guerard et al [ 26 ] and Kooy et al [ 27 ], using a comprehensive wellness assessment program or patient counselling combined with an electronic reminder device respectively, did not show any impact on statin adherence. Of note, although general results were inconclusive, Kooy et al [ 27 ] did report that using only the electronic reminder device had a positive effect on patient adherence in women in a secondary prevention setting (adjusted OR = 8.26 [2.20–31.0], p = 0.002).…”
Section: Resultsmentioning
confidence: 80%
“…Another study [ 27 ] reported a positive effect on adherence only in a sub-group of women who had the electronic reminder in a secondary prevention setting. The other two studies [ 26 , 33 ] reported no effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations